2020
DOI: 10.17509/jpki.v6i2.26292
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia in Nursing Students at Padjadjaran University

Abstract: During the industrial revolution of 4.0, everything becomes easily accessible. One of its developments is information and communication technology. The high use of a smartphone as communication tools can cause dependency which is characterized by repeatedly checking smartphones which can cause addiction so that it can cause fear or phobia, commonly known as Nomophobia. The aim of this study was to determine the overview of nomophobia in Nursing students at Padjadjaran University. This research used a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the international literature, there are studies that found moderate nomophobia in nursing students, as well as studies that achieved higher scores. 4,9 A study conducted by Gutiérrez-Puertas found that Portuguese nursing students felt more stress when their charges ran out, and their total nomophobia score was found to be 54.7. 4 In the same study, the nomophobia score of the Spanish students was found to be 35.4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the international literature, there are studies that found moderate nomophobia in nursing students, as well as studies that achieved higher scores. 4,9 A study conducted by Gutiérrez-Puertas found that Portuguese nursing students felt more stress when their charges ran out, and their total nomophobia score was found to be 54.7. 4 In the same study, the nomophobia score of the Spanish students was found to be 35.4.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Various studies have found that the 18-25 age group is at higher risk for nomophobia. 1,[9][10][11][12][13] In studies conducted with nursing students, determined that participants' communication levels decreased as their level of smartphone addiction increased. 1,12,14 Moreover, nomophobia was found to prevent healthcare professionals from communicating effectively with patients, cause misunderstandings, and reduce the quality of nursing care.…”
mentioning
confidence: 99%
“…At an advanced level, patients experience difficulties in their work performance, so they have to change jobs or resign. [1][2][3][4] According to data from the World Health If this is missed by health services, then problems can occur, such as refusing to receive treatment, not accepting body structure and function, reducing social contact, and negative feelings and views of the body and decisions. [5][6][7][8] This study aimed to explore the life experiences of breast cancer patients receiving chemotherapy at Jayapura General Hospital Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The number of nomophobia in Indonesia the age of 18-24 years has increased significantly, in 2013 individuals who experienced nomophobia were around 75% and in 2014 individuals who experienced nomophobia were around 84% (Rahayuningrum & Sary, 2019). Research conducted by Haryati et al, (2020). on 961 nursing students at Padjajaran University showed that 559 students (63.5%) experienced moderate nomophobia, 243 students (27.6%) experienced severe nomophobia and 79 students (9%) experienced mild nomophobia.…”
Section: Introductionmentioning
confidence: 99%